Economic Development and Environmental Degradation in ASEAN - M. Irsyad Ilham (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2018)
The economic development in ASEAN still declines environmental quality, whereas the worst environmental quality became negative externality reduce output in many sectors of ASEAN’s economy. This paper aimed to analyze the two-way relationship among economic development and environmental degradation in ASEAN with the factors which influenced it. This article used a panel data from eight ASEAN countries with the period of 2004 – 2013. The analysis method used simultaneous equation model. The results showed the two-way relationship between economic development and environmental degradation in ASEAN existed. Moreover, Gross Domestic Product (GDP) per capita and energy consumption had a positive impact on environmental degradation. Meanwhile, carbon dioxide emission per capita and trade openness had a positive effect on economic development. Therefore, the economic development strategy for ASEAN countries should be directed to increase GDP per capita and reduce the energy consumption.DOI: 10.15408/sjie.v7i1.6024